Fertilization with potassium (K) in the soybean-corn succession affects behavior of plants and in the soil (oxisol) - Cavalli, Edilson; Lange, Anderson; Cavalli, Cassiano; Bedin, Ivan; Buchelt, Antonio Carlos [UNESP]; Mellis, Estêvão Vicari (Southern Cross Publishing, 2019)
The potassium fertilizer recommendations are almost entirely made by the main culture in the field, without taking into account the predecessor and successor cultures. The nutrients in crop residues represent a reserve for subsequent crops. Therefore, knowledge of the absorption and cycling capacity of nutrient through the culture, and efficient fertilization should consider the entire system are important. This study aimed to evaluate the effect of potassium levels in soybean and corn, changes in nutrient stocks in the soil profile, absorption and accumulation in plant tissues and soybean, corn and Urochloa crop production during the two agricultural years. The study was performed in an oxisol in the cerrado-amazon ecotone, with potassium rates (0, 40, 80, 160 and 320 kg ha-1 K2O). The rates applied in soybean (first crop) and three harvests of residual effect of the applied doses (maize-soybeans-maize) were evaluated. After harvesting the first crop, plots were subdivided (with or without the presence of Urochloa in corn spacing) in order to understand effect of Urochloa to increase the potassium cycling in the system. The grain yield and dry matter of Urochloa, extraction, and export of nutrients and their concentration in the leaf were evaluated. During the experiment, the chemical changes caused in the soil were also evaluated. In the first year, corn yield and the cumulative grain yield of the other crops were increasingly influenced by K2O rates. The rates provided increased K concentration and a decrease in Ca and Mg in plant materials. The Ca and Mg elements showed a decreased trend in the soil influenced by the applied rates of up to 130 days after fertilization. The K showed higher levels influenced by rates even after 619 days. We do not recommend the application of high doses of K due to the large losses caused by leaching.
Keywords: Export; Extraction; Glycine max; Leaching; Residual effect; Zea mays